2006
DOI: 10.1111/j.1745-4549.2006.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Moisture Shelf-Stable Grated Carrot Product Using Hurdle Technology

Abstract: Carrot (Daucus carota) can be highly perishable and difficult to preserve fresh for long periods at ambient temperature and humidity. Studies on grated carrots were carried out for the development of a shelf‐stable moist‐preservation process based on infusion of additives using hurdle technology. Additives comprising 3.0% sodium chloride (to reduce water activity [Aw] to 0.94), 0.9% citric acid (to reduce pH to below 4.5), 1.0% sodium citrate and 0.2% sodium benzoate (as antimicrobial agents) were followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…The initial SPC load declined during storage due to the hurdle effect resulting in the changes in the microenvironment of the bacteria forcing them to lose 'homeostasis', essential for reproduction, resulting in inactivation (Leistner, 1994). As such, the multitarget preservation technique was found to be capable of keeping the sensory and microbial characteristics stable during the extended shelf-life (Vibhakara et al, 2006). The sulphitation of the product has been shown to cause microbial stability in addition to retention of the color attributes (Cerrutti et al, 1988).…”
Section: Shelf Stabilitymentioning
confidence: 97%
“…The initial SPC load declined during storage due to the hurdle effect resulting in the changes in the microenvironment of the bacteria forcing them to lose 'homeostasis', essential for reproduction, resulting in inactivation (Leistner, 1994). As such, the multitarget preservation technique was found to be capable of keeping the sensory and microbial characteristics stable during the extended shelf-life (Vibhakara et al, 2006). The sulphitation of the product has been shown to cause microbial stability in addition to retention of the color attributes (Cerrutti et al, 1988).…”
Section: Shelf Stabilitymentioning
confidence: 97%
“…Reducing a w value of foods by salt addition may lead to an extended lag phase, in which bacterial cells undergo a period of adaptation to the new environment before the exponential phase commences. Specifically, addition of a 3.6% salt solution to grated carrot was reported to reduce a w sufficiently (0.84) to suppress microbial growth within the product while maintaining an acceptable taste, however addition of 4% salt resulted in the product developing an excessively salty taste [12].…”
Section: Salt In Food Manufacturementioning
confidence: 99%
“…European Food Safety Authority has also approved the use of DST and TSC as permitted food additives and is added to the list of antioxidants with E numbers 335 and 331, respectively. It has been reported that sodium salts of citrate and tartarate are used as acidity regulators, food preservatives, anticaking agents, flavour enhancers, colour retention agents as well as stabilizers (Arslan, Ilhan, & Karabulut, 2006;Vibhkara, Gupta, Jayaraman, & Mohan, 2006). Another method for preventing food materials from putrefaction comprises the admixing of acetic acid and salts of citric, tartaric, malic as well as lactic acid (Shibata et al, 1980).…”
Section: Introductionmentioning
confidence: 97%